2023
DOI: 10.1371/journal.pone.0286363
|View full text |Cite
|
Sign up to set email alerts
|

Care delivery team composition effect on hospitalization risk in African Americans with congestive heart failure

Abstract: The care delivery team (CDT) is critical to providing care access and equity to patients who are disproportionately impacted by congestive heart failure (CHF). However, the specific clinical roles that are associated with care outcomes are unknown. The objective of this study was to examine the extent to which specific clinical roles within CDTs were associated with care outcomes in African Americans (AA) with CHF. Deidentified electronic medical record data were collected on 5,962 patients, representing 80,92… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Prior research has demonstrated that patients with the severest cases of CHF and CHF patients with signi cant comorbidity are heavy utilizers of health care systems as evident by their large combinations of clinical roles on their care teams during hospitalization, when compared to patients with other chronic conditions. 3,8,14 CHF patient care team con gurations generally include an array of general practitioners with broad care expertise and those with specialize expertise in CHF. 25 Overall, this study found no speci c care team con guration models (i.e., combination of clinical roles) consistently found to be statistically signi cant among both all patients and when strati ed by heart failure severity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior research has demonstrated that patients with the severest cases of CHF and CHF patients with signi cant comorbidity are heavy utilizers of health care systems as evident by their large combinations of clinical roles on their care teams during hospitalization, when compared to patients with other chronic conditions. 3,8,14 CHF patient care team con gurations generally include an array of general practitioners with broad care expertise and those with specialize expertise in CHF. 25 Overall, this study found no speci c care team con guration models (i.e., combination of clinical roles) consistently found to be statistically signi cant among both all patients and when strati ed by heart failure severity.…”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with the prior research demonstrating the vast and highly engaged role of the registered nurse in high quality CHF care delivery (e.g., immediate triage, ongoing monitoring, discharge planning, end-of-life care). 8,14,26 Furthermore, a recent study of 5,962 CHF patients found that CHF patients with a registered nurse providing care delivery was associated with an 88% decreased risk of having a hospitalization and 50% decreased risk of having a high of readmissions over a seven year period. 14 These ndings also demonstrate that the highly engaged role of registered nurses provide a signi cant opportunity for increased nurse-led solutions for reducing LOS and charges in CHF patients, as the ACC and AHA have called for care team recon guration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the University of Arkansas for Medical Sciences (UAMS), <7% of the faculty are minorities, which constrains efforts to engage URM communities using URM faculty for direct advocate-to-community engagement. In particular, it constrains biomedical research domains with a focus on cardiovascular and blood disorders, as heart disease is the leading cause of death in the United States, including individuals of most racial and ethnic groups ( 24 , 25 ). African Americans in Arkansas with reduced cardiovascular function have a significantly higher number of hospitalizations and readmissions than White Americans ( 26 , 27 ).…”
Section: Introductionmentioning
confidence: 99%